2013
DOI: 10.1186/2251-6832-4-9
|View full text |Cite
|
Sign up to set email alerts
|

Methanolysis optimization of sesame (Sesamum indicum) oil to biodiesel and fuel quality characterization

Abstract: Statistical approach was employed to optimize biodiesel production from sesame oil in this work. Precisely, response surface methodology was applied, and the effects of four variables, viz. reaction temperature, catalyst amount, reaction time, and methanol/oil molar ratio, and their reciprocal interactions were determined. Central composite rotatable design was used to generate a total of 30 individual experiments, which were designed to study the effects of these variables during alkali-catalyzed methanolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 26 publications
3
28
0
Order By: Relevance
“…All other terms displayed are not significant. The low values of standard error observed in the intercept and all the model terms demonstrated that the regression model fit the data, and the prediction was good [37]. The variance inflation factor (VIF) obtained in this study illustrates that the centre points are orthogonal to all other factors in the model.…”
Section: Gas Chromatographic Analysis Of T Peruviana Seed Oilmentioning
confidence: 76%
See 2 more Smart Citations
“…All other terms displayed are not significant. The low values of standard error observed in the intercept and all the model terms demonstrated that the regression model fit the data, and the prediction was good [37]. The variance inflation factor (VIF) obtained in this study illustrates that the centre points are orthogonal to all other factors in the model.…”
Section: Gas Chromatographic Analysis Of T Peruviana Seed Oilmentioning
confidence: 76%
“…The R 2 value is always between 0 and 1 [37,65]. However, for creating a good-fit model, it was recommended that R 2 should not be less than 80% [66].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Threedimensional (3D) response surface plots are representations, which graphically denote the regression equations for the optimization of reaction variables [19]. These surface plots in the present study are shown in Figures 2, 3, and 4.…”
Section: Analysis Of Surface Plots Of the Responsesmentioning
confidence: 99%
“…The larger the values, the stronger the significance of a factor on the process condition [18,19]. Based on the high value and low probability value, the decreasing order of significance of the selected factors is as follows: temperature > leaf powder : water ratio > time ; temperature > time > vegetable powder : water ratio ; temperature > leaf powder : water ratio > time , respectively, on the yield, TPC, and TAA of the polyphenol concentrates (Table 3).…”
Section: Optimization Of Polyphenol Concentrate Extraction Frommentioning
confidence: 99%